Flow Cytometric Assessment of the Morphological and Physiological Changes of Listeria monocytogenes and Escherichia coli in Response to Natural Antimicrobial Exposure - Braschi, Giacomo; Patrignani, Francesca; Siroli, Lorenzo; Lanciotti, Rosalba; Schlueter, Oliver; Froehling, Antje (Frontiers in Microbiology, 2018)
Essential oils (EOs) or their components represent one of the most promising natural, safe and feasible alternatives to prevent the growth of food-borne pathogens like Listeria monocytogenes and Escherichia coli in food matrixes. Although antimicrobial properties of EOs and their components are well documented, few and fragmented is the information about the changes on the physiological properties of microbial cells induced by the exposure to such compounds even at sub-lethal concentrations. The aim of this study was to explore the changes to the morpho-physiological properties of the cells of Listeria monocytogens Scott A and Escherichia coli MG 1655 induced after e one hour exposure to different sub-lethal and lethal concentrations of citral, carvacrol, (E)-2-hexenal and thyme EO. For this purpose different cell viability parameters, such as membrane integrity, esterase activity and cytoplasmic cell membrane potential were measured by flow cytometry. Flow cytometry data revealed specific response patterns in relation to the strain, the natural antimicrobial and its concentrations. Both the target microbial strains showed an increased cell membrane permeabilization without a loss of the esterase activity and cell membrane potential with increasing citral, carvacrol and thyme EO concentrations. By contrast, (E)-2-hexenal did not significantly affect the measured physiological properties of Listeria monocytogens Scott A and Escherichia coli MG 1655. The approach used allowed to identify the most effective natural antimicrobials in relation to the microbial target.